Whole-body cryostimulation limits overreaching in elite synchronized swimmers - Schaal, K.; Le Meur, Y.; Louis, J.; Filliard, J.-R.; Hellard, P.; Casazza, G.; Hausswirth, C. (Medicine & Science in Sports & Exercise, 2015)
Introduction: Elite athletes frequently undergo periods of intensified training (IT) within their normal training program. These periods can lead athletes into functional overreaching, characterized by high perceived fatigue, impaired sleep, and performance. Because whole-body cryostimulation (WBC) has been proven to be an effective recovery method in the short term (<76 h), we investigated whether daily WBC sessions during IT could prevent exercise and sleep-related signs of overreaching.